2017
DOI: 10.1039/c7ra02056b
|View full text |Cite
|
Sign up to set email alerts
|

Technological advances in current metabolomics and its application in tradition Chinese medicine

Abstract: During the last few years, many metabolomics technologies have been established in biomedical research for analyzing the changes of metabolite levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 88 publications
(82 reference statements)
0
16
0
1
Order By: Relevance
“…Metabolomics approach plays a key role in researching the metabolic disorder-related diseases (Zhang et al, 2013d;Zhang et al, 2014e;Zhang et al, 2015b;Sun et al, 2015;Zhao et al, 2016;Chu et al, 2016;Song et al, 2017;Ren et al, 2018;Qiu et al, 2020), discovery and identification of biomarkers (Zhang et al, 2014f) and treatment (Wang et al, 2012;Liang et al, 2015;Zhang et al, 2016b;Zhao et al, 2017;Liu et al, 2018;Sun et al, 2019;Wu et al, 2019;Qiu et al, 2020). Many biomarkers are being discovered for better understanding of metabolic mechanisms (Ma et al, 2016; and evaluating the efficacy diseases (Chu et al, 2015a;Chu et al, 2015b;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics approach plays a key role in researching the metabolic disorder-related diseases (Zhang et al, 2013d;Zhang et al, 2014e;Zhang et al, 2015b;Sun et al, 2015;Zhao et al, 2016;Chu et al, 2016;Song et al, 2017;Ren et al, 2018;Qiu et al, 2020), discovery and identification of biomarkers (Zhang et al, 2014f) and treatment (Wang et al, 2012;Liang et al, 2015;Zhang et al, 2016b;Zhao et al, 2017;Liu et al, 2018;Sun et al, 2019;Wu et al, 2019;Qiu et al, 2020). Many biomarkers are being discovered for better understanding of metabolic mechanisms (Ma et al, 2016; and evaluating the efficacy diseases (Chu et al, 2015a;Chu et al, 2015b;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics plays an important role in exploring metabolic disorder metabolism-related diseases, [18][19][20][21][22][23][24][25][26][27][28][29] biomarkers identication [30][31][32][33][34][35][36][37][38] and response to treatment. [39][40][41][42][43][44][45][46] In this study, differences in biomarkers in urine between the model group and the blank group were successfully analyzed and 25 biomarkers were ultimately associated with the CHD model.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that CHMs and their natural products possess many biological activities; anti-inammatory and antioxidative stress effects are the principal contributors to their pharmacological action. [116][117][118] However, it is worth mentioning that researchers have used omics techniques and methods to study the mechanism of RA in transgenic and induced arthritis animal models, and many of the results are satisfactory; however, these phenomena do not appear to be specic. In other words, it is found that the functions or inhibitory effects of CHMs and their natural products on these targets and pathways are also found for other diseases, not only RA, such as in the case of NF-kB, TNF-a and members of the interleukin family.…”
Section: Discussionmentioning
confidence: 99%